The Role of Rock Phosphate and Farm Yard Manure Combined-Phosphate-Solubilizing Bacteria in Increasing Nutrient Uptake and Soybean Yield - Aidi Noor (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2005)
The aims of the experiment were to evaluate the effect of rock phosphate application and combination betweenphosphate-solubilizing bacteria with farm yard manure on nutrient uptake and yield of soybean. Factorial experiment design with two factors was used in randomized complzte block design with three replications. The first factors was level of rockphosphate i.e. : 0; 30; 60; 90 kg P ha· I, and the second factor was combination of phosphate solubili=ing bacteria andfarm yard manure: without phosphate solubi/i=ing bacteria andfarm yard manure; phosphate solubilbing bacteria (Pseudomonas fluorescens); farm yard manure 10 ton ha